HACCP - Mortimore, Sara.; Wallace, Carol (UK : John Wiley, 2015)
"Readers of this accessible book - now in a revised and updated new edition - are taken on a conceptual journey which passes every milestone and important feature of the HACCP landscape at a pace which is comfortable and productive. The information and ideas contained in the book will enable food industry managers and executives to take their new-found knowledge into the workplace for use in the development and implementation of HACCP systems appropriate for their products and manufacturing processes.The material is structured so that the reader can quickly assimilate the essentials of the topic. Clearly presented, this HACCP briefing includes checklists, bullet points, flow charts, schematic diagrams for quick reference, and at the start of each section the authors have provided useful key points summary boxes. HACCP: a Food Industry Briefing is an introductory-level text for readers who are unfamiliar with the subject either because they have never come across it or because they need to be reminded. The book will also make a valuable addition to material used in staff training and is an excellent core text for HACCP courses"--
Includes index.
Keywords: Hazard Analysis and Critical Control Point (Food safety system); Food adulteration and inspection; Food handling -- Safety measures; TECHNOLOGY & ENGINEERING / Food Science